Metaphor of Sound - Lee Breuer’s Gospel at Colonus - Rozik, Eli (Recherches sémiotiques / Semiotic Inquiry, 2015)
Lee Breuer’s Gospel at Colonus is an attempt to achieve a synthesis between an ancient Greek tragedy and the black Pentecostal church service, in addition to offering a mixed marriage between white and black cultural idioms. Regarding this experiment, the question is not, I believe, reducible to Breuer’s intention so much as the actual result of the work itself. Indeed, in experimenting with culturally established styles of expression, results depend on the nature of their unprecedented interaction. Therefore, hermeneutic inquiry is rather problematic and perhaps only a learned intuition is possible as a starting point. Nonetheless, I conjecture that rendering the narrative of Sophocles’ Oedipus at Colonus through the prism of Gospel music bestows an additional metaphoric dimension on the basic metaphor embodied in the original play-script. This study aims at elucidating the nature of these metaphoric dimensions, specifically on the level of sound.